2022
DOI: 10.24171/j.phrp.2022.0243
|View full text |Cite
|
Sign up to set email alerts
|

mRNA vaccine effectiveness against SARS-CoV-2 B.1.617.2 (Delta) and B.1.1.529 (Omicron) variant transmission from home care cases to household contacts in South Korea

Abstract: Objectives: Household contacts of confirmed cases of coronavirus disease 2019 (COVID-19) are exposed to a high risk of viral transmission, and secondary incidence is an important indicator of community transmission. This study analyzed the secondary attack rate and mRNA vaccine effectiveness against transmission (VET) for index cases (patients treated at home) confirmed to be infected with the Delta and Omicron variants.Methods: The subjects of the study were 4,450 index cases and 10,382 household contacts. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This study confirmed, similar to previous findings, that the SAR of unvaccinated groups was higher than that of vaccinated groups during both the Delta and Omicron periods [ 14 , 16 ]. Other countries reported a risk of infection 1.4 to 2.5 times higher among unvaccinated groups [ 8 , 16 , 18 , 19 ], which agrees with a study that showed a higher risk of infection among unvaccinated Koreans [ 9 ]. Additionally, a study conducted in Spain reported that COVID-19 vaccination was effective during the Delta period [ 26 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study confirmed, similar to previous findings, that the SAR of unvaccinated groups was higher than that of vaccinated groups during both the Delta and Omicron periods [ 14 , 16 ]. Other countries reported a risk of infection 1.4 to 2.5 times higher among unvaccinated groups [ 8 , 16 , 18 , 19 ], which agrees with a study that showed a higher risk of infection among unvaccinated Koreans [ 9 ]. Additionally, a study conducted in Spain reported that COVID-19 vaccination was effective during the Delta period [ 26 ].…”
Section: Discussionsupporting
confidence: 87%
“…Although a previous study investigated SARs in Korea by COVID-19 vaccination status, the result predated the Omicron period and did not analyze risk factors such as reinfection and age group [ 9 ]. The current study used the large datasets reported to the CIMS during the Delta and Omicron periods, identifying risk factors such as age group, vaccination status, and reinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suicidal ideation and planning are important predictors of suicide [ 43 ], appropriate monitoring and interventions are needed to prevent an increase in suicide rates due to prolonged COVID-19 measures. The incidence of COVID-19 is decreasing because of the development of vaccines and treatments [ 44 , 45 ]; however, problems associated with the after-effects of the disease are emerging [ 11 ]. Our findings can serve as a basis for formulating appropriate policies and government measures to protect Korean youth from the potential side-effects of the COVID-19 pandemic that could impair the rest of their lives.…”
Section: Discussionmentioning
confidence: 99%
“…As of February 7, 2023, according to the Global In uenza Surveillance and Response System (GISAID), 7,458,737 Omicron genome sequences were shared by 209 countries, and the Omicron variant was reported to have triggered the fourth and fth waves of COVID-19 worldwide [4,5]. Vaccine effectiveness and vaccine effectiveness against transmission (VET) for Omicron mutations have been con rmed; but [6,7], COVID-19-con rmed cases and deaths continue to occur worldwide [3]. As of January 18, 2023, the number of cumulative global con rmed cases and deaths were 663,001,898 and 6,707,959, respectively, with a mortality rate of 84 per 100,000 and a fatality rate of 1.0% [8].…”
Section: Introductionmentioning
confidence: 99%